In vitro behaviour of curcumin nanoemulsions stabilized by biopolymer emulsifiers: Effect of interfacial composition - Pinheiro, A. C. (2016)
Nanoemulsions present a high potential to be used in food products due to their advantages over conventional emulsions (e.g. higher stability to gravitational separation and droplet aggregation and enhanced bioavailability of encapsulated compounds), however their application to foods is hindered by some concerns about potential risks associated with their ingestion. The knowledge of the behaviour of nanoemulsions as well as the fate of bioactive compounds encapsulated within them in the gastrointestinal (GI) tract is of utmost importance to assess their safety for human consumption and to produce delivery systems that provide an optimized bioactivity of the encapsulated compound. In this work, a dynamic gastrointestinal model, comprising the simulation of stomach, duodenum, jejunum and ileum, was used to evaluate the behaviour of curcumin nanoemulsions stabilized by biopolymer emulsifiers (lactoferrin and lactoferrin/alginate multilayer structure) under GI conditions. The interfacial characteristics of curcumin nanoemulsions had a significant impact on their physicochemical stability within the simulated GI tract. Also, results suggested that alginate coating may be able to control the rate of lipid digestion and free fatty acids adsorption within the GI tract, but the encapsulated lipid is digested at the same extent, releasing the lipophilic bioactive compound. This work contributes to an improved understanding of how multilayer nanoemulsions behave within the GI tract and this knowledge will be useful for the optimization of delivery systems that improve the physicochemical stability of emulsions in food products, while still releasing encapsulated lipophilic bioactive compounds.